The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/bip.21283
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐dependent folding and unfolding of ligand‐bound purine riboswitches

Abstract: Riboswitch regulation of gene expression requires ligand-mediated RNA folding. From the fluorescence lifetime distribution of bound 2-aminopurine ligand, we resolve three RNA conformers (C(o), C(i), C(c)) of the liganded G- and A-sensing riboswitches from Bacillus subtilis. The ligand binding affinities, and sensitivity to Mg(2+), together with results from mutagenesis, suggest that C(o) and C(i) are partially unfolded species compromised in key loop-loop interactions present in the fully folded C(c). These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…Experimental studies have shown that binding of the ligand to the riboswitch leads to tightening and stabilization of the tertiary interactions between L2 and L3 2933; 35; 47 Hence, the two models of the apo forms of the riboswitch, A1 and A2 , developed in this study represent two extremes of the experimental regimen, with the results obtained from the individual simulations allowing for interpretation of the available experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have shown that binding of the ligand to the riboswitch leads to tightening and stabilization of the tertiary interactions between L2 and L3 2933; 35; 47 Hence, the two models of the apo forms of the riboswitch, A1 and A2 , developed in this study represent two extremes of the experimental regimen, with the results obtained from the individual simulations allowing for interpretation of the available experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…However, when docking is compromised, e.g. at low concentrations of Mg 2+ ions, ligand binding may not be sufficient to dock the aptamer structure, leading to an array of coexisting and partially docked ligand-bound states that differ in local and global tertiary structure as recently suggested by stopped-flow (54), sm-FRET (22) and ultra-fast time-resolved spectroscopy (36,37). In this context, funneling this ensemble of stiff-liganded states towards a tightly packed mRNA-ligand complex, resembling the X-ray structure (20), may require assistance from specifically trapped divalent metal ions along the docking pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The folding of the aptamer domain has been investigated using a number of experimental techniques including NMR [57, 95, 96], smFRET [52, 56], chemical probing [51], fast fluorescence spectroscopy [97, 98], single molecule force extension spectroscopy [91, 99, 100], as well as molecular dynamics simulation [101-104]. While all of these techniques observe different aspects of the folding process, together they yield a reasonably consistent model of the folding process.…”
Section: Folding Of the Riboswitchmentioning
confidence: 99%